Practices of Teachers' Motivation in Community College - Chhetri, Ashmita Dahal (Nepalese Journal of Management Research, 2022)
This paper entitled, "Practices of Teachers’ Motivation in Community College” was conducted in Chitwan district of Nepal. Exploring what practices are enacting while motivating the teachers in community colleges from an unexplored context provides important and critical information for scholars. In this context, this study explored the motivational practices for teacher’s motivation in community colleges in Nepal. Three out of twelve community colleges of Chitwan district were selected for this study. Teachers were taken as the respondents for the study. This study adapted focused interview design of qualitative approach.The verbal data or information generated from different respondents using semi-structured and open-ended interview questionnaires were analyzed and interpreted with reference to Herzberg's dual factor theory and Stacy Adams equity theory. Finding of the study, revealed that community college in Nepal are attempting to motivate their teachers to adopt widely used good practices as in other organizations of similar nature. However, they are unable to implement those practices as per the expectations of their teachers due to insufficient resources and lack of systematized procedures. Those college are seeking more support from their affiliating universities, University Grand Commission and also from the state, province and local government.